PRODUKSI ASAM LEMAK DARI MINYAK KELAPA SAWIT DENGAN PROSES HIDROLISIS - Setyopratomo, Puguh (Jurnal Teknik Kimia, 2012)
In this research work fatty acid was produced by hydrolysis of crude palm oil using hydrochloric acid catalyst. The hydrolysis was performed in 1 liter stirred spherical glass reactor. Agitation speed was maintained at 450 rpm, whereas oil bath was used to maintain the reaction mixture temperature. The reaction mixture temperature was varied at 40 oC, 60 oC, and 80 oC, whereas crude palm oil/ water mol ratio was varied at 1:3, 1:6, 1:9, and 1:12. The experiment results showed that the reaction equilibrium had not been achieved yet after the reaction running for 8 hours. The highest conversion was 69.77% which was obtained at reaction temperature 80 oC and crude palm oil/water mol ratio 1:12. The experiment results also showed that the reaction temperature and water excess significantly affecting the reaction conversion. Key words: crude palm oil, fatty acid, hydrolysis, HCL